Late relapses in primary CNS lymphoma after complete remissions with high-dose methotrexate monotherapy. (December 2015) - Ambady, Prakash; Holdhoff, Matthias; Bonekamp, David; Wong, Fay; Grossman, Stuart A
Treatment of patients with newly diagnosed primary CNS lymphomas using high dose methotrexate regimens is reported to yield about 30% long term survivors with minimal neurotoxicity. As in other systemic large cell lymphomas, it is generally assumed that most relapses occur within 5 years of diagnosis. A retrospective review of the Johns Hopkins experience in 52 patients treated between 1995 and 2008 yielded 19 patients (37%) who achieved a complete response and were followed for over 5 years. Four of these patients remained progression-free for over 10 years. However, two of these long-term survivors have now relapsed over 10 years after their initial diagnosis. An analysis of progression and overall survival does not reveal a plateau suggesting that even patients who have not recurred for over 10 years remain at high risk for relapse after treatment with single agent high dose methotrexate.